N-Pyrazinylhydroxybenzamides as biologically active compounds: a hit-expansion study and antimicrobial evaluation - Kerda, Marek; Šlechta, Petr; Jand'ourek, Ondrej; Konečná, Klara; Hatoková, Paulina; Paterová, Pavla; Zitko, Jan (Future medicinal chemistry, 2023)
Background: The development of novel antimicrobial drugs is an essential part of combatting the uprising of antimicrobial resistance. Proper hit-to-lead development is crucially needed. Methods & results: We present a hit-expansion study of N-pyrazinyl- and N-pyridyl-hydroxybenzamides with a comprehensive determination of structure-activity relationships. The antimicrobial screening revealed high selectivity to staphylococci along with antimycobacterial activity with the best value of 6.25 μg/ml against Mycobacterium tuberculosis H37Rv. We proved an inhibition of proteosynthesis and a membrane depolarization of methicillin-resistant Staphylococcus aureus. Conclusion: Our results are a good starting point for further development of new antimicrobial compounds, where the next step would be tuning the potential between relatively nonspecific membrane depolarization effect and specific inhibition of proteosynthesis.
Keywords: macromolecular assay; Methicillin-Resistant Staphylococcus aureus; Anti-Infective Agents; structure–activity relationship; membrane depolarization; Anti-Bacterial Agents; mikrobiální testy citlivosti; hit expansion; antiinfekční látky; Microbial Sensitivity Tests; antimicrobial resistance; minimum bactericidal concentration; antimycobacterial; antibacterial; water solubility; antibakteriální látky; Staphylococcus; methicilin rezistentní Staphylococcus aureus